Malaysia foreign exchange rate depreciation does political stability matters? - Lim, Chin Yang; Lai, Yi Khang; Chua, Jian Hean; Lim, John Zhe Meng (2020)
This study examines the weakening of the foreign exchange rate in Malaysia. The country will be heavily impacted by the weakening of the Malaysian foreign exchange rate. The economic variables of the foreign exchange rate should be researched in order to maintain a stable exchange rate. The annual data consisting of 30 sample size which includes five economic variables and political variables, ranging from 1970 to 2018. Real interest rate, inflation rate, foreign direct investment, export, financial crisis and political stability are variables. The data was derived from data from the World Bank. Autoregressive distributed lag (ARDL) was used to evaluate the relation between the foreign exchange rate and the independent variables. This study examines the factors influencing the foreign exchange rate in order to avoid the economic problems from occurring. In addition, this study will provide some useful information for those parties involved in it, such as investors, governments, policy makers and international researchers, to gain a better understanding of the foreign exchange rate.